(untitled) (Journal of Asian Development Studies, 2023)
This study examines the traditional teaching methods employed in large classes within public sector colleges in Punjab at the intermediate level. Additionally, it proposes alternative approaches and strategies for instructors to manage large English classes effectively. Data was collected using a survey research strategy, employing mixed-method research techniques. Qualitative data were gathered through interviews with English teachers from selected public sector boys’ colleges in major cities of Punjab. Quantitative data were collected via a questionnaire with closed-ended items administered to students within the study sample. Three public sector colleges from the target population were randomly selected for data collection. The study utilized six structured interviews with English teachers and received 60 completed questionnaires from intermediate students as data collection tools. To enhance outcomes in large language classes, teachers should concentrate on activity-based teaching, collaborative instruction, and the utilization of group work or interactive approaches. There is a pressing need for government intervention to facilitate the improvement and advancement of public sector colleges.